Rainfall and ways of managing and investing: A study in the development of water resources in Muthanna Governorate (Badia Al Samawah) - Hassan Abed, Falah; Al–Khafaji, Sarhan Naeem (Al-Adab Journal, 2021)
This study aims at transforming rainwater from human and economic risk to a source of water that can be utilized in the desert of Muthanna Governorate (Badia Samawah) which suffers from large water deficit, and offer proposals to benefit from flood waters and harvest rain water directly. Because the rainy season is limited and limited to the winter in Iraq, it was necessary to work seriously to benefit from every drop of rain water and not to lose it. The efficiency of the limited use of rainwater for the cultivation of the land and to provide the necessary food for the inhabitants of these areas, and this exploitation is by the state and individuals alike, but the burden is on the state because of its potential to facilitate this process, Work to maximize the use of rainwater in a rational and accurate manner. Directing efforts to maximize the use of rainwater in the Badia requires interaction, enthusiasm, disciplined activity, accuracy, follow-up and careful commitment. As well as respect for the responsibility of water management and the perception of the risk of complacency, complacency, and negative consequences on humans and the environment. The problem of water shortage, population growth and consumption requires us to invest rainwater in the Badia as part of a true national aquatic wealth.